Characterization and expression of the gene glucose transporter 2 (GLUT2) in embryonic, larval and adult Bay snook Petenia splendida (Cichliformes: Cichlidae) - Castillo-Collado,Alejandra del Carmen (2022)
Abstract Bay snook (Petenia splendida) is a carnivorous cichlid species with excellent economic value in Southeast Mexico. Although this species presents an excellent potential for commercial aquaculture, the information about its nutritional, physiological, and reproductive metabolic pathways is meager. The current study focuses on the expression of glucose transporter 2 (glut2) in embryos and larvae at 5, 10, 15-, 20-, 25-, and 30-days post-hatch (dph) and in the liver, intestine, kidney, muscle, heart, testicle, gill, stomach, pancreas, and brain of adult fish. The partial sequence of glut2 was obtained, and specific qPCR primers were designed. In embryos, the expression was lower compared to larvae at 5, 15, and 20 dph. The highest expression in larvae occurred at 20 dph and the lowest at 25 and 30 dph. Maximum expression levels in adults occurred in the liver and intestine. Our results show that glut2 is expressed differentially across tissues of adult bay snook, and it fluctuates during larval development.